Endemics and our Medical Sciences in the Past and Present: Lessons from the Prophetic Traditions - Khan, Muhammad Kalim Ullah; Rubina (Al-Irfan, 2021)
The COVID-19 that affected much of the planet is a tragedy without precedent. In this way I will address the biographical answer and solution to this endemic, explicitly through the Holy Prophet Muhammad (SAAS) traditions. I'm discussing one of the most non-experimental blames on Islamic Traditional Sciences that they do not concentrate on catastrophic diseases like epidemics or endemics and do not fix the problem with respect to the medical sciences that actually solve the problem. I contend against this idea that in Islamic Classical Sciences explicitly Prophet Muhammad’s traditions (SAAS) provide a solution to our everyday problem whether it belongs to healthcare or to other issues. In addition, this article discusses whether Islam relies on scientific discovery or on purely spiritual understandings. It also addresses the scientific, ontological and eschatological teachings of the Prophet Muhammad (SAAS) towards the issue.